Overtourism di Kawasan Perkotaan: Sebuah Systematic Literature Review dengan Analisis Bibliometrik menggunakan VOS Viewer (2015-2025) - Aisyah Asri Nurrahma; Dyah Isyana Lastri; Eka Putri Wulandari; Wirdatul Khomro Septian Candra (Jurnal Penelitian Ilmu Pariwisata, 2026)
Overtourism has emerged as a highly debated phenomenon in tourism studies, particularly within urban tourism dynamics. It occurs when the negative impacts of tourism begin to outweigh its benefits for a destination. Driven by a scarcity of research examining its formation, impacts, and relationship with sustainability, this study maps the literature development on urban overtourism using a Systematic Literature Review (SLR) approach. Data were collected from the Scopus database (2015–2025). Following rigorous selection, 167 eligible articles were extracted and analyzed using VOSviewer and Biblioshiny to map research trends and keyword co-occurrence networks. The bibliometric analysis identified four main thematic clusters: shifts in tourist motivations, urban tourism governance, structural socio-economic impacts, and tourism sustainability. This study concludes that although current overtourism research is predominantly Eurocentric, such studies remain vital for fostering adaptive urban governance to mitigate negative impacts and ensure the overall sustainability of urban tourism.